20 GHz self‐oscillating parametric optical frequency comb generator using an electroabsorption modulated laser based dual‐loop optoelectronic oscillator. Issue 6 (1st December 2020) - Cheng, Yumin; Yan, Juanjuan
Abstract : In this work, a self‐oscillating parametric optical frequency comb generator is proposed and experimentally demonstrated. It consists of an electroabsorption modulated laser (EML) based dual‐loop optoelectronic oscillation loop and a parametric frequency mixer. In the experiments, a 20 GHz radio‐frequency signal is produced to drive the EML. The output pulses from the EML are amplified to work as pump seeds for the frequency mixer. In the mixer, a length of high non‐linear fibre (HNLF) is firstly used to introduce chirps to the pump pulses, a section of single mode fibre is then employed for pulse compression, and finally another HNLF is applied for parametric frequency mixing. When the pump power is 28 dBm, a nine‐line comb with a frequency spacing of 20 GHz and an optical signal‐to‐noise ratio >15 dB is generated. More comb lines can be obtained when another frequency mixer is cascaded.